Novel cobalt(II) coordination complexes based on 3, 4, 5-trifluorobenzeneseleninic acid and different N-donor ligands. (15th May 2018) - Yan, Mao; Zhang, Ru-Fen; Zhang, Shao-Liang; Ru, Jing; Du, Ji-Yuan; Ma, Chun-Lin
Graphical abstract: Three novel cobalt(II) coordination complexes constructed by 3, 4, 5-trifluorobenzeneseleninic acid (L) and different N-donor ligands, namely, [Co(4, 4′-bpy)(L)2 ] n (1 ), [Co(2, 2′-bpy)(L)2 ] n (2 ), [Co2 (en)4 (L)2 (NO3 )4 ]·(CH3 CN)2 (3 ). (4, 4′-bpy = 4, 4′-bipyridine, 2, 2′-bpy = 2, 2′-bipyridine, and en = ethylenediamine) have been designed, synthesized and characterized by IR spectroscopy, elemental analysis, single-crystal X-ray diffraction analyses. In the three complexes above, the 3, 4, 5-trifluorobenzeneseleninic acid ligand adopt anti–anti bridging coordination mode and all the cobalt ions show distorted octahedral configurations. Complex1 displays a 2D layer structure, which is further connected by π⋯π interactions to give rise to a 3D supramolecular structure. The structure of complex2 exhibits 1D tube-like double chain structure and the neighboring chains are further linked by hydrogen-bonds C–H⋯F and π⋯π interactions to form a 3D supramolecular structure. However, complex3 is a monomer which can be connected into a 2D supramolecular layer through the intermolecular C–H⋯O hydrogen-bonds interaction. In addition, the magnetic properties of complexes1 and2 are characterized. Abstract: Three novel cobalt(II) coordination complexes constructed by 3, 4, 5-trifluorobenzeneseleninic acid (L) and different N-donor ligands, namely, [Co(4, 4′-bpy)(L)2 ] n (1 ), [Co(2, 2′-bpy)(L)2 ] n (2 ), [Co2 (en)4 (L)2 (NO3 )4 ]·(CH3 CN)2 (3 ). (4, 4′-bpy = 4, 4′-bipyridine, 2, 2′-bpy = 2, 2′-bipyridine, and en = ethylenediamine) have been designed, synthesized and characterized by IR spectroscopy, elemental analysis, single-crystal X-ray diffraction analyses. In the three complexes above, the 3, 4, 5-trifluorobenzeneseleninic acid ligand adopt anti–anti bridging coordination mode and all the cobalt ions show distorted octahedral configurations. Complex1 displays a 2D layer structure, which is further connected by π⋯π interactions to give rise to a 3D supramolecular structure. The structure of complex2 exhibits 1D tube-like double chain structure and the neighboring chains are further linked by hydrogen-bonds C–H⋯F and π⋯π interactions to form a 3D supramolecular structure. However, complex3 is a monomer which can be connected into a 2D supramolecular layer through the intermolecular C–H⋯O hydrogen-bonds interaction. In addition, the magnetic properties of complexes1 and2 are characterized.